2021
DOI: 10.3389/fimmu.2021.780779
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Extrachromosomal Circular DNA in Human Placentas With Fetal Growth Restriction

Abstract: Many studies have confirmed that extrachromosomal circular DNAs (eccDNAs/ecDNAs) exist in tumor and normal cells independently of the chromosome and are essential for oncogene plasticity and drug resistance. Studies have confirmed that there are many eccDNAs/ecDNAs in maternal plasma derived from the fetus. Fetal growth restriction (FGR) is a pregnancy-related disease associated with high newborn morbidity and mortality. However, the characteristics and nature of eccDNAs/ecDNAs in FGR are poorly understood. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 98 publications
1
12
1
Order By: Relevance
“…Additionally, both maternal and fetal eccDNA profiles had a 10 bp periodicity, which is consistent with our findings. 19 , 22 The shift in eccDNA size distribution in cancer patients may be caused by changes in the microenvironment, and the underlying mechanisms warrant further research. According to prior research, eccDNA may play important roles in tumor incidence and progression, tumor heterogeneity and tumor oncogene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, both maternal and fetal eccDNA profiles had a 10 bp periodicity, which is consistent with our findings. 19 , 22 The shift in eccDNA size distribution in cancer patients may be caused by changes in the microenvironment, and the underlying mechanisms warrant further research. According to prior research, eccDNA may play important roles in tumor incidence and progression, tumor heterogeneity and tumor oncogene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…It provided a new vision for the screening of new biomarkers for FGR. 286 Neidlinger C et al detected significantly more spcDNAs in the angiofibroma-derived cell cultures of patients with tuberous sclerosis (TS) than in the skin of these patients or in the skin of 11 healthy donors. 287 Motejlek K et al further found that the spcDNA from angiofibroma cultures was much longer than that from skin fibroblast cultures.…”
Section: Potential Applications Of Eccdnamentioning
confidence: 99%
“…However, important differences were identified between normal pregnancy and fetal growth restriction patients. A noticeable difference was the total number of eccDNAs, which was slightly higher than the control group ( Yang et al, 2021a ). Biological function analysis revealed apoptosis might play an important role in fetal growth restriction, which could, to some extent, relate to the shallow implantation of placental trophoblast cells ( Paules et al, 2019 ).…”
Section: Eccdna In Human Diseasesmentioning
confidence: 67%
“…Such findings are not restricted to the plasma. According to a study by Yang et al, human placenta-derived eccDNAs also contained two peaks at 146 and 340 bp, and double-repeated trinucleotide sequences were equally present on both sides of these circular molecules ( Yang et al, 2021a ). In addition, their sequencing data revealed that the repertoires of eccDNAs in the placenta overlapped considerably with chromosomal regions, including gene regions, CpG islands, introns, and transposable elements (TEs).…”
Section: Eccdna In Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation